Interaction between lactose and cadmium chloride in aqueous solutions as seen by diffusion coefficients measurements - Verissimo, Luis M. P. (2013)
Diffusion coefficients of an aqueous system containing cadmium chloride 0.100 mol · dm−3 and lactose at different concentrations at 25 °C have been measured, using a conductimetric cell and an automatic apparatus to follow diffusion. The cell relies on an open-ended capillary method and a conductimetric technique is used to follow the diffusion process by measuring the resistance of a solution inside the capillaries, at recorded times. From these results and by ab initio calculations, it was possible to obtain a better understanding of the effect of lactose on transport of cadmium chloride in aqueous solutions.